Transparency and Accountability of Campaign Funds in the 2014, 2019, and 2024 Elections in Indonesia - Habibi, Muhammad (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2024)
This study examines the significance of campaign fund management in the implementation of elections in Indonesia, specifically in the 2014, 2019, and 2024 general elections. Based on existing regulations, such as Law No. 7 of 2017 and General Election Commission Regulation (PKPU) No. 18 of 2023, campaign funds are a strategic element supporting various campaign activities, including the production of promotional materials, logistics, and campaign events. However, the implementation of these regulations faces several challenges, particularly regarding the transparency of fund reporting and oversight of social media campaigns. Through an analysis of campaign fund receipts and expenditures by political parties participating in the elections, this study finds that the size of campaign funds does not always correlate directly with electoral success. Success in elections is also determined by effective campaign strategies, candidate integrity, and the relevance of political programs. Furthermore, the complexity of the digital era introduces new challenges in overseeing campaign funds, such as the proliferation of anonymous accounts on social media that are difficult to monitor. This study recommends strengthening the role of oversight bodies such as the General Election Commission (KPU) and the Election Supervisory Body (Bawaslu) through the establishment of specialized digital monitoring subunits and the development of data-driven technology. These steps are expected to enhance transparency, accountability, and public trust in the electoral process while ensuring the integrity of democracy in Indonesia.